Sufi Educational Narratives in Wasiat Renungan Masa by TGKH. Muhammad Zainuddin Abdul Madjid - Lalu Gede Muhammad Zainuddin Atsani; Ulyan Nasri; Muzakkir Walad; Lalu Fauzi Haryadi; Hakkul Yakin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
The findings of the research indicate that “Wasiat Renungan Masa” contains various narratives of Sufi education that impart spiritual values, ethics, and life concepts within the Sufi tradition. These narratives encompass teachings on the unity of God, the individual's relationship with God, the significance of divine love, submission, as well as spiritual practices that embrace simplicity and introspection. This research provides a deeper understanding of how the narratives of Sufi education within “Wasiat Renungan Masa” reflect and convey the values of Sufism as taught by TGKH. Muhammad Zainuddin Abdul Madjid. The implications of this research offer insights into how Sufi teachings can be applied in daily life and how these narratives can influence the spiritual growth and ethics of individuals.